2021
DOI: 10.1007/s11125-020-09533-7
|View full text |Cite
|
Sign up to set email alerts
|

A touchstone of Finnish curriculum thought and core curriculum for basic education: Reviewing the current situation and imagining the future

Abstract: Pandemics, like other global challenges, are unquestionably curricular issues. They are curriculum issues not only because of the disrupting consequences of Covid-19 and the economic and social crisis alike but also because people have, through their own activities, contributed to global catastrophes and perpetuated injustices. This article attempts to answer the question: How does Finnish curricular thought, including the role of the teacher and the core curriculum for basic education, respond to the various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…(NCCBE) 2016) emphasising generic, transversal skills, e.g. critical thinking, future skills and multiliteracies as well as teacher collaboration and integration across subjects (Hakala and Kujala 2021;Haapaniemi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(NCCBE) 2016) emphasising generic, transversal skills, e.g. critical thinking, future skills and multiliteracies as well as teacher collaboration and integration across subjects (Hakala and Kujala 2021;Haapaniemi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Gorski 2016a; Pennington et al 2013) have been suggested to capture the overarching issues and qualities. In teacher education, these notions could potentially be supported by the increasing emphasis on generic skills and competences over subject-matter-based objectives in curricula at different levels (Hakala and Kujala 2021;Harju and Niemi 2018;Toom and Husu 2018). In the context of intercultural teacher education, Dervin, Moloney, and Simpson (2020) suggested using 'competences', in the plural, to recognise the various dimensions of teachers' intercultural competence.…”
Section: Teachers' Equity Literacymentioning
confidence: 99%
“…F I G U R E 1 Structure of the Finnish national core curriculum of basic education Thus, if we seek to understand the emergence of any particular curriculum version, the complex histories that characterize how a school or a subject function must also be understood (Brady & Kennedy, 1999). As previous research has shown, the desired curricular goal in PE is to shape the students' bodies to conform to the requirements of particular sports, which goes back to the strong role of extracurricular sports in the past (Giese & Ruin, 2018;Hakala & Kujala, 2021). Until emphasizing the educational goals of PE in the current curricular shift in Finland (FNBE, 2016) and internationally, normative expectation of a healthy and functioning body capable of performing at a high level has been idealized in curriculum documents (Giese & Ruin, 2018).…”
Section: A Curriculum For Students With Sen -The Perspecti Ve Of Ableismmentioning
confidence: 99%
“…Cultural diversity and gender quality are promoted for the first time in the current PE curriculum, as stated above (FNBE, 2016). As pointed out by Hakala and Kujala (2021), previous Finnish PE curricula entirely excluded cultural diversity until 2014.…”
Section: Understanding Inclusionmentioning
confidence: 99%
See 1 more Smart Citation